2014
DOI: 10.1182/blood-2014-04-569046
|View full text |Cite
|
Sign up to set email alerts
|

MiR-146a regulates the TRAF6/TNF-axis in donor T cells during GVHD

Abstract: Key Points This study deciphers the regulatory role of miR-146a during GVHD in mice. In humans, the minor genotype of the SNP rs2910164, which reduces expression of miR-146a, was associated with higher GVHD severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 38 publications
7
88
0
Order By: Relevance
“…Interleukin (IL)-6 plays a central role in GVHD and has recently been shown to be a targetable factor. 25 We observed significantly reduced IL-6 levels in the serum of mice that received Cav-1 2/2 T cells compared with WT T cells ( Figure 2C). …”
Section: Lack Of Cav-1 Expression Of the Donor T Cells Decreases Gvhdmentioning
confidence: 79%
“…Interleukin (IL)-6 plays a central role in GVHD and has recently been shown to be a targetable factor. 25 We observed significantly reduced IL-6 levels in the serum of mice that received Cav-1 2/2 T cells compared with WT T cells ( Figure 2C). …”
Section: Lack Of Cav-1 Expression Of the Donor T Cells Decreases Gvhdmentioning
confidence: 79%
“…25,41 However, few expanded human tTregs expressed IFN-g under our conditions, and expression was not affected by miR146b-5p antagomir treatment (supplemental Figure 2). Because control CD4 T cells also expressed miR-146b-5p, albeit at low levels, it seemed possible that downmodulation of this miRNA would induce Foxp3 expression and suppressive function.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of miR-155 in donor T cells leads to increased GvHD mortality, whereas miR-155 deficiency prevents aGvHD (4). Furthermore, increased miR-146a expression in donor T cells prevents from GvHD development by targeting TNFR-associated factor 6, leading to reduced TNF transcription (5). It has also been shown that blocking the miR17-92 cluster alleviates aGvHD while preserving the graftversus-leukemia (GvL) effect (6).…”
mentioning
confidence: 99%